Upaya Pengolahan Sampah Anorganik di Kelurahan Pangkalan Kasai dengan Pembuatan Ecobrick - Zulkarnain, Zulkarnain; Ismail, Ahmad; Septian, Rizky; Syahputra, Andriyan; Mungianty, Nesty; Putrianti, Rini; Junisa, Sisilia; Marito, Pinitta; Xaverius, Fransiskus; Delani, Yosinda; Maulida, Olivia (Unri Conference Series: Community Engagement, 2024)
The most significant problem with plastic materials is their non-biodegradable waste. It takes a very long time to clean up plastic waste, and its utilization is almost impossible to manage. Plastics also contribute to rising air temperatures due to their non-porous polymer properties. Ecobricks are a creative effort to manage plastic waste by turning it into useful items that can reduce pollution. The process of making ecobricks involves collecting, cleaning, and packing plastic waste tightly into plastic bottles. This process extends the lifespan of the plastic and repurposes it into something beneficial for human use. The method used is qualitative, involving observation with the 3R strategy: Reduce, Reuse, and Recycle. The making of ecobricks is still not very popular among the public. Most people still treat used plastic as household waste, which can pollute the environment. Ecobricks can be used as crafting materials with marketable value. The results of these ecobricks include chairs and trash bins, which are then distributed to TK Pertiwi and the Kapau Lake tourist site in Pangkalan Kasai Village